2013
DOI: 10.1155/2013/948181
|View full text |Cite
|
Sign up to set email alerts
|

ADSPPMutation Causing Dentinogenesis Imperfecta and Characterization of the Mutational Effect

Abstract: Mutations in the DSPP gene have been identified in nonsyndromic hereditary dentin defects, but the genotype-phenotype correlations are not fully understood. Recently, it has been demonstrated that the mutations of DSPP affecting the IPV leader sequence result in mutant DSPP retention in rough endoplasmic reticulum (ER). In this study, we identified a Korean family with dentinogenesis imperfecta type III. To identify the disease causing mutation in this family, we performed mutational analysis based on candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…This is in accordance with the results obtained from PolyPhen‐2, suggesting a Probably Damaging and SignalP suggesting defective signal peptide cleavage site recognition. The findings are supported by functional studies (Hart & Hart, ; Lee et al., ) indicating a retention of the Pro17 mutated protein in the ER and proposing a dominant negative effect due to cellular stress and reduction in protein export.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This is in accordance with the results obtained from PolyPhen‐2, suggesting a Probably Damaging and SignalP suggesting defective signal peptide cleavage site recognition. The findings are supported by functional studies (Hart & Hart, ; Lee et al., ) indicating a retention of the Pro17 mutated protein in the ER and proposing a dominant negative effect due to cellular stress and reduction in protein export.…”
Section: Discussionsupporting
confidence: 58%
“…The enamel has been reported to be normal in structure and mineral content (Malmgren, Lundberg, & Lindskog, 1998). However, Lee et al (2013), Wang et al (2011) andBloch-Zupan et al (2016) reported the enamel to be hypoplastic. Furthermore, in teeth with DI-II, the supportive dentin layer is dysplastic and has been associated with a brittle enamel that is more prone to fracture (Finn, 1962).…”
Section: Introductionmentioning
confidence: 99%
“…57 Towards a nosology defined by mutations spectrum To date 38 pathological variants have been described in the DSPP gene, located in the peptide signal region, within the DSP region and within the DPP region (Table 2). 1,7,28,43,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Most of them (28) leads to DGI-II, eight to DD-II and two to DGI-III. No mutation has been described within the DGP coding region.…”
Section: Dentin Dysplasia Type I or Radicularmentioning
confidence: 99%
“…Several other genes associated with dentin formation are considered candidate genes for hereditary dentin defects; however, only mutations in DSPP have been shown to result in DGI-II, DGI-III and DD-II (Xiao et al, 2001;Zhang et al, 2001Zhang et al, , 2007Zhang et al, , 2011Rajpar et al, 2002;Kim et al, 2004Kim et al, , 2005Malmgren et al, 2004;Dong et al, 2005;Holappa et al, 2006;Song et al, 2006Song et al, , 2008Lee et al, 2008Lee et al, , 2009Lee et al, , 2011aLee et al, , 2013McKnight et al, 2008a,b;Kida et al, 2009;Wang et al, 2009;Bai et al, 2010;Nieminen et al, 2011;Li et al, 2012;Liu et al, 2016;Yang et al, 2016). Therefore, the three diseases seem to be allelic with varying phenotypes.…”
Section: Introductionmentioning
confidence: 99%